Couples coping in the community after the stroke of a spouse: A scoping review. Issue 2 (16th November 2019) - Ramazanu, Sheena; Loke, Alice Yuen; Chiang, Vico Chung Lim
Abstract: Aim: To summarize evidence on the poststroke coping experiences of stroke patients and spousal caregivers living at home in the community. Design: A scoping review. Methods: Extensive searches were conducted in credible databases. Articles published in the English language were retrieved. Data were extracted based on study location, aims, study design, sample size, time after stroke and key findings. Results: Out of 53 identified articles, 17 studies were included in the review. Five key themes were as follows: (a) emotional challenges; (b) role conflicts; (c) lack of strategies in coping; (d) decreased life satisfaction of the couples; and (e) marriage relationship: at a point of change. Couples were not sufficiently prepared to cope and manage with stroke at home on discharge from the hospital. This review emphasized the need for hospitals to implement policies to address the inadequate preparation of couples in coping with stroke.